Holistic Care for Sleep Quality and Mental Health of Postnatal Mothers - Fitriana Yuni Permana Sari; Marni Marni; Rovica Probowati; Titin Syahwarani; Putri Kusuma Romadhani (International Journal Of Health Science, 2026)
The postpartum period is an important and vulnerable time for the health of mothers after childbirth. Data shows that the prevalence of sleep disorders and the risk of postpartum depression globally is 14%, in Asia 26-85%, and in Indonesia 50-70%. At the Gatak Community Health Center, integrated holistic interventions for sleep quality and mental health are limited. This study aims to examine the effect of holistic care on PSQI and EPDS in postpartum mothers through interventions consisting of relaxation techniques, education, and psychosocial support. Methods: A quasi-experimental one-group pretest-posttest design and purposive sampling were used on 15 postpartum mothers with the criteria of age 18-40 years, 1-6 weeks postpartum, good communication skills, and signing an informed consent form. Results: Paired t-test analysis (p<0.05) showed a significant effect of holistic care on the sleep quality and mental health of postpartum mothers through a comparison of pretest-posttest means. Conclusion: Holistic care is effective in reducing cortisol, improving sleep hygiene and social support, and can be implemented in primary care settings in Indonesia. Recommendations: Integrate PSQI/EPDS into maternal and child health guidelines, conduct training for midwives, and conduct further research using RCTs.